Higher intakes of flavonoids are associated with lower salivary IL‐1β and maintenance of periodontal health 3–4 years after scaling and root planing. (13th February 2020) - Sparrow, Taylor V.; Dodington, David W.; Yumol, Jenalyn L.; Fritz, Peter C.; Ward, Wendy E.
Abstract: Aims: Higher intakes of fruits and vegetables, and vitamin C are associated with improved periodontal healing post‐scaling and root planing (SRP). This study determined if this association was sustained at 3–4 years post‐SRP, and if flavonoid intake is associated with periodontal health. Whether reduced probing depth (PD) is sustained and whether PD is correlated with salivary IL‐1β, IL‐6 and CRP at 3–4 years post‐SRP were also studied. Materials and Methods: Clinical periodontal outcomes, dietary intakes and salivary markers of inflammation were measured in patients ( n = 43, 23 females, 37–93 years) who had undergone SRP 3–4 years earlier and had been part of a periodontal maintenance programme. Results: Flavonoid intake was inversely associated with PD ( p = .042) and salivary IL‐1β concentration ( p = .015) after adjustment for multiple confounders. When changes in PD were considered, the association of flavonoid intake with reduced PD became borderline significant ( p = .051) but persisted for IL‐1β ( p = .018). PD at 3–4 years and 2–4 months post‐SRP was similar. There was a positive correlation between PD and salivary IL‐1β ( p = .005) but not with salivary CRP and IL‐6. Conclusion: Higher flavonoid intake is associated with lower IL‐1β. Also, regular supportive periodontal therapy maintained the improved PD at 3–4 years post‐SRP regardless of smoking status.